The unrealised promises of education: the challenges of school to work transition in Ethiopia - Tafere, Y; Chuta, N (Young Lives, 2020)
This working paper focuses on how young men and women make the transition from school to work and the problems they encounter in doing so. It draws on Young Lives longitudinal qualitative and survey data which document the link between education and work over time.